Local community's support for post-tsunami recovery efforts in an agrarian village and a tourist destination: a comparative analysis - Babu P. George (Community Development Journal. 2007, 2007)
The present paper examines the local community's support for the post-tsunami recovery of two affected places in India: one a tourist destination and the other an agrarian village. The investigation begins with the proposition that social capital is a vital influence upon local communities' willingness to support tsunami recovery efforts. The underlying assumption was that the resident community at the agrarian village with its rich social capital and tradition of community activities would proactively participate in the reconstruction program and thereby make a speedier and more meaningful recovery than the resident community at the tourist destination. However, an empiricalsurvey conducted to prove this point provided us with contradictory results: the survey revealed no significant difference in the levels of social capital across the communities. Consequently, the researchers carried out a focus group discussion with the locals at the tourist destination. The interesting conclusion is that it is probably the richness of the very same social capital that provoked local participation at the agrarian village and eliminated it at the tourist destination